2008
DOI: 10.1189/jlb.0907611
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating myeloid-derived suppressor cells are pleiotropic-inflamed monocytes/macrophages that bear M1- and M2-type characteristics

Abstract: Here, tumor-infiltrating CD11b(+) myelomonocytoid cells in murine colon adenocarcinoma-38 and GL261 murine glioma were phenotypically characterized. Over 90% were of the CD11b(+)F4/80(+) monocyte/macrophage lineage. They also had a myeloid-derived suppressor cell (MDSC) phenotype, as they suppressed the proliferation of activated splenic CD8(+) T cells and had a CD11b(+)CD11c(+)Gr-1(low)IL-4Ralpha(+) phenotype. In addition, the cells expressed CX(3)CR1 and CCR2 simultaneously, which are the markers of an infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
251
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(272 citation statements)
references
References 27 publications
12
251
1
5
Order By: Relevance
“…[45][46][47][48] Along these lines, it has been demonstrated that the TGFb inhibitor, SM16, acts to inhibit its kinase activity and, in turn, skews unfavorable MDSCs to become tumoricidal myeloid cells. 9 The SHP1 inhibitor, NSC87877, can similarly shift the activity of MDSCs, 49 resulting in reduced tumor growth. The exact mechanism by which these pathways regulate MDSC polarization remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48] Along these lines, it has been demonstrated that the TGFb inhibitor, SM16, acts to inhibit its kinase activity and, in turn, skews unfavorable MDSCs to become tumoricidal myeloid cells. 9 The SHP1 inhibitor, NSC87877, can similarly shift the activity of MDSCs, 49 resulting in reduced tumor growth. The exact mechanism by which these pathways regulate MDSC polarization remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…7 MDSCs have been classified by their surface marker expression profiles into distinct subsets and are typically characterized as either CD1-1b C Ly6G C Ly6C ¡/low granulocytic MDSCs (GMDSCs) or CD11b C Ly6G ¡/low Ly6C high monocytic MDSCs (MO-MDSCs) with diverse functions in tumor and other tissues. [7][8][9][10] Several cytokines and chemokines are implicated in the recruitment of myeloid cells to the tumor, including colonystimulating factor-1 (CSF-1). [8][9][10][11] CSF-1 signaling through its receptor CSF-1R is a critical regulator of survival, differentiation and proliferation of myeloid cells and their precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokine system plays critical roles for the migration as well as the activation in various types of cells. Regarding the chemotaxis of MDSCs, recent reports show C-C chemokine receptor 2 (CCR2) regulates the dynamics in tumor environment (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, Umemura et al showed that tumor-infiltrating MDSCs are pleiotropic-inflamed macrophages that can simultaneously display both M1-and M2-characteristics. 15 In contrast, it has been shown that M2-type MDSCs can be skewed toward M1-type cells by lipopolysaccharide (LPS) through the p38 mitogen-activated protein kinases (MAPK) pathway, 16 further underlining the plasticity of these cells. Thus, it is clear that MDSCs display a high degree of plasticity and that their exact fate will be determined by various factors inherent to the tumor type.…”
Section: Introductionmentioning
confidence: 99%